Formic acid-aided sample preparation method for sensitive and simultaneous analysis of eight nitrosamines in poorly-water soluble pharmaceutical drugs using liquid chromatography–ultraviolet detection - Eiichi Yamamoto; Hitomi Kan-no; Daisuke Ando; Tamaki Miyazaki; Tatsuo Koide; Ken-ichi Izutsu; Yoji Sato (Journal of Pharmaceutical and Biomedical Analysis Open)
There has been a growing concern over the contamination of pharmaceutical products with nitrosamines (NAs) such as N-nitrosodimethylamine (NDMA). To quantify NA levels in drugs using reversed-phase liquid chromatography (LC), the sample solution should achieve a high drug concentration to detect trace NAs, and an appropriate amount of hydrophilic NAs should be retained. However, these are difficult to achieve, and no suitable method has yet been developed. The present study was the first to develop a sample preparation method to achieve this by combining drugs with formic acid (FA), followed by the removal of active pharmaceutical ingredients (APIs) from samples via crystallization. This method was successfully applied for the sensitive quantification of eight NAs in poorly water-soluble acidic atorvastatin (ATS) and basic itraconazole (ITC) via LC–ultraviolet (LC-UV) detection. The removal rate of ITC via recrystallization exceeded 99.96 %, whereas most NAs remained as solutes. Assuming that the enhancement in ITC solubility directly translates to heightened analytical sensitivity, a > 100-fold increase in sensitivity was attained compared to conventional methodologies. This sample preparation method would be applicable to other poorly water-soluble drugs, contributing to the control of NA content in various formulations to realize the safe delivery of pharmaceuticals to patients.